Penerapan PICSIMLab Simulator Sebagai Upaya Peningkatan Aktivitas Dan Hasil Belajar Peserta Didik Kelas XII Teknik Ototronik 1 SMKN 1 Sawit - Astuti, Sri Miyati (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2022)
This study aims to determine and describe (1) the application of the Project Based Learning learning model assisted by the PICSIMLab simulator software in increasing student activity in the subject of Electronic Control System Design on Vehicles in class XII Autotronic Engineering 1 SMKN 1 Sawit (2) Application of Project Based learning models PICSIM Lab simulator software assisted learning in improving student learning outcomes in the subject of Electronic Control System Design for Vehicles in class XII Autotronic Engineering 1 SMKN 1 Sawit. This research is a Classroom Action Research and conducted in two cycles which aims to determine the management of learning by the teacher, student activities, student learning outcomes, and the responses of class XII students of Autotronic Engineering at SMKN 1 Sawit. This study consisted of two cycles, each cycle consisting of planning, action, observation, and reflection. The implementation of the action uses computer-assisted interactive media with the question-and-answer learning method and discussion. The results showed that the application of the PICSIMLab simulator could increase the activity and learning outcomes of class XII students of Autotronic Engineering 1 in the subject of Electronic Control System Design on Vehicles. The results of the first cycle of action were compared with the results of the second cycle of action. Student activities that appear from all activities, which appear according to indicators have increased, in the first cycle as much as 75%, in the second cycle 87.5%. The average number of student activities in the first cycle was 64.5%, in the second cycle it was 85.3%. The assessment of student learning outcomes in this study was in the form of a post test. Classical learning outcomes in each cycle 79.67% and 92.53%.